Beyond equity: Advocating theory-based health promotion in parallel with COVID-19 mass vaccination campaigns - Ala'a B. Al-Tammemi; Zeinab Tarhini (Elsevier, 2021)
Despite the challenges in managing the COVID-19 pandemic waves in different contexts and capacities, the vaccines that were recently approved for use have created a window of hope to fight this pandemic more effectively by achieving herd immunity. However, the rates of vaccination coverage vary considerably between countries. While looking at COVID-19 vaccination from a different perspective, it brings up the following question: is equitable vaccine delivery and access the only critical issue? Assessing facilitators and barriers to successful vaccination initiatives should be carefully considered and addressed by subsequent actions. The COVID-19 vaccination campaigns as part of disease prevention programs could be embedded in the core of theories for a more systematic approach to enhance vaccine acceptance among people. For effective implementation of public health programs, it is imperative to understand human health behaviours and to have sufficient knowledge about cultural and environmental influences. Sufficient and satisfactory COVID-19 vaccine uptake is not only challenged by the availability of vaccines or their distribution, but also by cultural and social norms in the community as well as the complexity of human behaviours. Therefore, the global efforts should target communities with theory-based health promotion and awareness programs in parallel with vaccination campaigns as a part of public health practice.